The Effect of Program to Reduce Blood Sugar on Knowledge Motivation and Food Selective Skill in Women with Diabetic Mellitus Patients with Uncontrolled Blood Sugar - Anonjarn, Kanlayawee; Boonkerd, Sumonthip; Sukrueangkul, Alongkorn; Panthonglang, Warissara (Journal of The Royal Thai Army Nurses, 2023)
This quasi-experimental research aimed to study the effects of using the program for reduce blood sugar levels on knowledge, motivation, and food selection skills in female diabetic patients who can’t control their blood sugar levels by applying the Information Motivation Behavior skill model. The sample was Diabetes Mellitus type2 female patients with HbA1C ≥7 or higher who came to receive services at the Diabetes Clinic, Community Health Center, Muang Ratchasima Hospital. They were divided into experimental and comparison groups of 40 people each. Data were collected from questionnaire responses consisted of knowledge, motivation, food selection skills. and program to reduce blood sugar. Comparison of HbA1C levels before and after the experiment. and analyzed using frequency distribution, percentage number, Pair t-test, Independent t-test, and Repeated measures ANOVA statistics. The results showed that the experimental group had average knowledge, motivation, and food selection skills scores after joining the program more incredible than before joining the program (p-value < .05) and more significant than the comparison group (p-value < .05). After joining the program more than the comparison group (p-value < .05). After the experiment and the follow-up period in the experimental group, the cumulative blood glucose level was higher than before the experiment. When comparing the mean by repeated ANOVA, it was found that the cumulative blood sugar level between the experimental group and the comparison group. There was a statistically significant difference (F = 1497.882, df = 1, p-value < .01).